Taxonomic review of the Goblin spiders of the genus Dysderoides fage and their Himalayan relatives of the genera Trilacuna Tong and Li and Himalayana, new genus (Araneae: Oonopidae) - Grismado, Cristian José (2014)
The study of many museum specimens of goblin spiders from the Himalayan range and neighboring countries allows for the description of new taxa of the family Oonopidae. The genus Dysderoides Fage is taxonomically reviewed. It comprises small, blind, loricate troglobitic spiders: the type species (D. typhlos Fage, from India) and at least five new species from northern India (D. synrang Grismado and Deeleman) and Thailand (D. muang Grismado and Deeleman, D. kaew Grismado and Deeleman, D. kanoi Grismado and Deeleman, and D. lawa Grismado and Deeleman). The genus Trilacuna, previously known from China, Thailand, Malaysia, and Sumatra, is newly diagnosed by the loss of the furrow connecting the posterior spiracles in males, and is represented in the Himalayan region by seven species: T. aenobarba (Brignoli), from Bhutan (here transferred from Epectris Simon), and six new: four from northern India (T. meghalaya Grismado and Piacentini, T. besucheti Grismado and Piacentini, T. mahanadi Grismado and Piacentini, and T. loebli Grismado and Piacentini), one from India and Nepal (T. bangla Grismado and Ramírez), and one from Pakistan (T. hazara Grismado and Ramírez). The new genus Himalayana Grismado comprises species very similar to those of Trilacuna, but differs in the characters of the postepigastric scuta and by having an additional acute dorso-prolateral projection on the male palpi. Six new species are assigned to Himalayana: H. kathmandu Grismado (type species), H. castanopsis Grismado, H. parbat Grismado, and H. martensi Grismado (all from Nepal); and H. siliwalae Grismado and H. andreae Grismado (from India). The study of the internal female genitalia of T. meghalaya and T. bangla revealed a complex copulatory system, and an entelegyne condition, apparently uniform for the entire genus and probably for Dysderoides and Himalayana as well. The males of the three genera have a complex set of paraembolic laminae with brushes of filiform structures, among which discharges a gland through a thin, tortuous cuticular tube. The genitalic and somatic morphology of the three genera suggest that they conform a monophyletic group, here named “Dysderoides complex,” and that their closer relatives can be found among Prethopalpus Baehr et al., and other genera related to Silhouettella Benoit. The loss of the membranous diagonal area on the base of the anterior lateral spinnerets is proposed as a synapomorphy of an advanced group of loricatae oonopids usually referred as gamasomorphines. Furthermore Triaeris glenniei Fage, described from a single female from a cave in Uttarakhand, is redescribed and transferred to Camptoscaphiella Caporiacco.